Legal High? The High Stakes REgulatory Questions About Delta-8 THC & Other Emerging Psychoactive Cannabinoids - Owen Flomberg (Washington University Journal of Law and Policy, 2023)
The 2018 Farm Bill legalized hemp federally, thus marking a dramatic change in federal policy regarding cannabis. The legalization of hemp has led to the rapid proliferation of an intoxicating hemp-derived substance called Delta-8 THC in various products at gas stations, corner markets, and smoke shops across the United States. Delta-8 is only slightly chemically different from Delta-9 THC which is unambiguously illegal under federal law and is the better-known compound in cannabis that gets a user “high.” A regulatory gap has developed where the federal government regulates Delta-9 THC but not the various other compounds in the cannabis plant that have entered the market. This note argues that Congress must act to mandate and empower the Federal Drug Administration to regulate Delta-8 and other cannabinoids, not to ban them, but to facilitate their safe and responsible usage.
Keywords: THC; Hemp; Legalization; Farm Bill; Cannabis; FDA; Cannabinoids